(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Good and services tax (GST) is the biggest and substantial indirect tax reform since 1947. The main idea of GST is to replace existing taxes like value-added tax, excise duty, service tax and sales tax. It will be levied on manufacture sale and consumption of goods and services. GST is expected to address the cascading effect of the existing tax structure and result in uniting the country economically. The paper highlights the background, objectives of the proposed GST and the impact of GST in the present tax scenario in India, The paper further explores various benefits and opportunities of GST. Finally, the paper examines and draws out a conclusion.